Technological competency assessment - (:unkn) unknown (INDERSCIENCE ENTERPRISES LTD, 2019)
Technological competency assessment has become one of the most important issues in small and medium sized enterprises, particularly in manufacturing industry. The main motivation for assessing the technological infrastructure of an enterprise as a corporate competency is that it provides a faster and higher quality presentation of products and services through the discovery and utilisation of newer technological knowledge. Note that, assessing the technological competency will bring about various benefits not only to the enterprises but also to fund providers. In this study, a conceptual model is proposed for evaluating the technological deficiencies and highlighting the need for possible improvements. Four core components of technological capability such as machinery, IT systems, manufacturing support operations, storage and distribution are considered. The model has a nested structure and presents an evolutionary approach for assessing the state of the art and related progress. The details of the model are provided in the paper.
Keywords: technologic assessment; competency assessment; technological competency; enterprise assessment; small and medium sized enterprises; SMEs; MANAGEMENT; INNOVATION; MODEL